Wunderlich Syndrome: Early misdiagnosis with acute renal colic during COVID-19 pandemic - Reza Mohammadian; Afsoon Akbari; Mohmmadjavad Rajabi; Saman Nikeghbalian; Mahmood Shariat; Ahmad Monabati; Seyed Hamidreza Hosseinialhashemi (Bulletin of Emergency and Trauma, 2023)
Wunderlich syndrome, also known as the spontaneous non-traumatic retroperitoneal hemorrhage, is anuncommon condition characterized by acute, spontaneous, non-traumatic renal hemorrhage into the subcapsularor perirenal spaces. The majority of the cases are caused by renal cell carcinoma or renal angiomyolipoma.Other causes are arteriovenous malformation, cystic renal disease, and anticoagulation medications. Theclassic presentation is “Lenk’s triad” of acute flank pain, palpable flank mass, and hypovolemia. The diagnosisis based on clinical suspicion and confirmed by a CT scan, which is the preferred imaging modality. Due tothe rarity of these cases and the wide range of clinical manifestations, the treatment is divergent ranging fromconservative management to nephrectomy. Herein, we present a case of massive right renal hemorrhage causedby warfarin toxicity that was initially misdiagnosed as acute renal colic due to the patient’s refusal to refer tothe clinic during Corona Virus Disease- 19 era and was later managed with a right nephrectomy.